PENGARUH PENEMPATAN KERJA TERHADAP PRESTASI KERJA BAGIAN PEGAWAI ADMINISTRASI (Studi Pada Kantor Pusat PT. Perkebunan Nusantara V Pekanbaru) - Bobbi Tinambunan; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was conducted at PT. Perkebunan Nusantara V Pekanbaru. The problems in this study is the job performance that employees give not maximal can be seen from the level of employee absenteeism that every year there is always change and even increase, this is allegedly influenced by work placement that is less precise. The purpose of this study to determine the effect of work placement on employee job performance of the administration of PT. Perkebunan Nusantara Pekanbaru.In this research the method used is descriptive quantitative with SPSS program. The sample of this study was taken as many as 60 respondents from 148 population calculated using Slovin formula. Methods of data collection using questionnaires. Hypothesis testing using simple regression analysis method with result of research that is Y = 10.463 + 0.835X. The research that has been done shows that the responses of respondents to work placement and job performance of employees in good category. While for t test that has been done show that work placement variable by parsial have significant effect to work achievement. And for calculation of coefficient of determination () obtained R Square value equal to 0,607. This shows that the work placement gives influence of 60,7% to the job performance, while the rest 39,3% influenced by other variable not examined in this research. Keywords: Work Placement, and Job Performance.